2022
DOI: 10.1108/tlo-09-2022-0100
|View full text |Cite
|
Sign up to set email alerts
|

Training value, employee internal states and training transfer: examining the web of relationships

Abstract: Purpose This study aims to examine the web of relationships among training value, employee internal states (psychological empowerment, employee engagement and motivation to transfer) and training transfer. Design/methodology/approach Data is obtained from different categories of employees a few months after attending different training programs organized by their organization. Structural equation modeling is used to analyze the data. Bias-corrected and accelerated (BCa) confidence intervals are used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Motivation to transfer should not be underestimated in training transfer studies as this study has further supported the centrality of motivation to transfer in transmitting training transfer as espoused in the literature e.g. Andoh et al (2022c), Gegenfurtner et al (2009), Reinhold et al (2018) and Richter and Kauffeld (2020). This confirms the assertion that when there is no motivation to transfer, training transfer would most likely not occur irrespective of the availability of other factors (Gegenfurtner et al , 2009, 2020; Testers et al , 2015; Paulsen and Kauffeld, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Motivation to transfer should not be underestimated in training transfer studies as this study has further supported the centrality of motivation to transfer in transmitting training transfer as espoused in the literature e.g. Andoh et al (2022c), Gegenfurtner et al (2009), Reinhold et al (2018) and Richter and Kauffeld (2020). This confirms the assertion that when there is no motivation to transfer, training transfer would most likely not occur irrespective of the availability of other factors (Gegenfurtner et al , 2009, 2020; Testers et al , 2015; Paulsen and Kauffeld, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, in the meta-analytic study they conducted,Reinhold et al (2018) found the motivation to transfer to be a strong predictor of training transfer. Furthermore, motivation to transfer is thought to be a dynamic phenomenon and is proposed as a central factor that mediates antecedents in the training process and training transfer(Andoh et al, 2022c;Gegenfurtner et al, 2009;Reinhold et al., Training transfer process 2018; Richter and Kauffeld, 2020). Similarly, Seiberling and Kauffeld (2017) indicate that motivation to transfer is a mediator in numerous training transfer studies.…”
mentioning
confidence: 99%
“…According to Azmee and Kassim (2019), learning activities are essential in organisations. This is because they influence training transfer and employee outcomes such as employee empowerment and engagement (Andoh et al, 2022b) which are needed by organisations to be successful. For instance, empowered employees are high in confidence, self-reliant, creative, and participate in decision-making (Hieu, 2020;Kumar and Kumar, 2017).…”
Section: Customised Capacity Building and Learningmentioning
confidence: 99%
“…The issue of training transfer into actual performance often being low is a well-known and problematic area for many companies that invest in professional development. The study by Andoh et al (2022) sought to provide further evidence on how training actually affects implementation of the skills acquired. The authors provide further exploration that could help practitioners identify what makes employees use the results of their training.…”
Section: Training Humour and Embracing Mistakesmentioning
confidence: 99%
“…This implication for practitioners’ paper is based on Issue 6 from the previous 2022 volume. The articles from Issue 6 explored training transfer (Andoh et al, 2022), team diversity and humour (Batt-Rawden & Traavik, 2022), knowledge exchange and knowledge hiding (Kucharska and Rebelo, 2022), research on stability of personality traits and its relation to triple-loop learning (Fahrenbach & Kragulj, 2022), as well as case studies on interorganisational learning (Pareliussen et al, 2022) and strategic alliances (Ferrigno et al, 2022). The Issue 6 concludes with a Wraae (2021) book review exploring entrepreneurship education (Fust, 2022).…”
mentioning
confidence: 99%